The Development of a Progressive In Vitro Cell-Based Model of Osteoarthritis. - Blasioli, Dominick. (2017)
Abstract: Osteoarthritis (OA) of the knee, characterized by knee pain and eventual loss of joint function remains a significant unmet medical need worldwide. Treatment of both pain and structural damage progression are challenging, with current pain therapies providing inconsistent benefit and treatments to halt or slow loss of structural integrity nonexistent. Although the facets of OA are not well understood, it is clear that the disease represents a complex combination of metabolic processes affecting the cartilage, underlying bone, synovium, and surrounding tissues of articular joints. This complexity makes it difficult to develop accurate models. Given the cost, time, and complexity associated with performing in vivo studies, preliminary study of disease biology as well as identification, validation, and testing of potential therapeutic targets can benefit greatly from studies initially performed in vitro in well-designed models ideally translatable to both in vivo research and clinical settings. A human cell-based model of osteoarthritis progressing from early to late-stage OA was developed. This work included the combination of synovial fibroblasts and monocytes as a model of synovium. In culture with the synovium component, mesenchymal stem cell (MSC) pellets were used as the cartilage component. At early time points, the model produced many cytokines and degradative enzymes present in clinical OA. Glycosaminoglycan (GAG) was released from the cartilage component. Also, the cartilage component mounted a repair response as measured by an increase in aggrecan gene expression. These three criteria were evidence of a model of early stage OA. At later time points, the cartilage component continued to lose GAG. The repair response was lost. Finally, the production of degradative enzymes, specifically matrix metalloproteinase 1 and 3 (MMP-1 and MMP-3), was diminished. These criteria were evidence of a progression to late stage OA. Understanding the full progression of OA could lead to the development of new targets and new therapeutics and having a realistic in vitro model is one step in that process.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: Catherine Kuo, Li Zeng, and Gloria Matthews.; Keyword: Biomedical engineering.